The practice : shipping creative work - Godin, Seth (Penguin Business, 2020)
For any artist, entrepreneur, or visionary who feels stuck, Seth Godin has a simple answer- commit to the practice. In this revolutionary little book, Seth Godin will turn your assumptions about the creative process upside down and help you to look at the world from a different angle. You will recognize your work for what it is- an act of generosity and a way to make change, as well as what it can never be, something that will make everyone happy. The Practice will help you dance with your fear, take the risks worth taking and embrace the empathy required to make work that connects with others. This breakthrough book will show you a path forward, encourage intent in every facet of your work and help you seek out constraints. You'll walk away with practical strategies for overpowering the naysayers, radically trusting your own voice and finally doing the work you were put on this earth to do.